[2 + 2 + 1] Cycloaddition of N-tosylhydrazones, tert-butyl nitrite and alkenes: a general and practical access to isoxazolines. Issue 28 (28th June 2021) - Ma, Liang; Jin, Feng; Cheng, Xionglve; Tao, Suyan; Jiang, Gangzhong; Li, Xingxing; Yang, Jinwei; Bao, Xiaoguang; Wan, Xiaobing
Abstract : A novel [2 + 2 + 1] cycloaddition of N -tosylhydrazones, tert -butyl nitrite and alkenes was successfully established, which allowed facile construction of a wide range of isoxazolines. Abstract : N -Tosylhydrazones have proven to be versatile synthons over the past several decades. However, to our knowledge, the construction of isoxazolines based on N -tosylhydrazones has not been examined. Herein, we report the first demonstrations of [2 + 2 + 1] cycloaddition reactions that allow the facile synthesis of isoxazolines, employing N -tosylhydrazones, tert -butyl nitrite (TBN) and alkenes as reactants. This process represents a new type of cycloaddition reaction with a distinct mechanism that does not involve the participation of nitrile oxides. This approach is both general and practical and exhibits a wide substrate scope, nearly universal functional group compatibility, tolerance of moisture and air, the potential for functionalization of complex bioactive molecules and is readily scaled up. Both control experiments and theoretical calculations indicate that this transformation proceeds via the in situ generation of a nitronate from the coupling of N -tosylhydrazone and TBN, followed by cycloaddition with an alkene and subsequent elimination of a tert -butyloxy group to give the desired isoxazoline.